An investigation of Thai students’ English language writing difficulties and their use of writing strategies - POONYAPAT BOONYARATTANASOONTORN (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aims to learn more about the struggles undergraduate students in Thailand have when writing in the English language and the strategies they employ to overcome those difficulties.Methodology: Using a questionnaire with five-point Likert scale items, 157 students enrolled in an intermediate English course provided quantitative data for this study. The data was analyzed with the help of the mean score, the standard deviation, and a chi-square test.Findings: According to the findings, the student’s writing skills were significantly below par, with the majority of complaints focusing on grammar. It was also discovered that the subjects routinely used cognitive strategies, most notably resourcing. There was no correlation between students’ writing proficiency and the types of writing strategies they employed.Implications/Novelty: Teachers, curriculum developers, and policymakers can use the results to better understand their students’ struggles with written English. It also emphasizes the importance of teaching students writing strategies so they can employ them to overcome any writing challenges they may encounter.